Different methods of dental caries diagnosis in an epidemiological setting - Renato Pereira da Silva; Andréa Videira Assaf; Gláucia Maria Bovi Ambrosano; Fábio Luiz Mialhe; Marcelo de Castro Meneghim (Universidade Estadual de Campinas, 2015)
Aim: To evaluate the performance of dental caries detection when adjunct methods are associated and their applicability in epidemiological survey of dental caries, at D3 (cavitated carious lesions at dentin layer) and D1+D3 (non cavitated and cavitated carious lesions at enamel/dentin layer) diagnostic thresholds. Methods: A total of 2189 posterior teeth from 165 12-year-old schoolchildren underwent visual examination without (CL1) and with artificial lighting (CL2), radiographic bitewing (BW), fiber-optic transillumination/FOTI (FT), DIAGNOdentTM (DD) and associations of these methods. Reproducibility was calculated by Kappa statistics and validity was calculated by sensitivity, specificity and accuracy tests. ANOVA (Scott-Knott test) was performed in order to compare the average values of DMF-S obtained by the diagnostic methods. Results: The CL2FTDDBW (D3) and CL2BW (D1+D3) exams presented the highest values for accuracy at epidemiological setting. The DMF-S index obtained for those exams was statistically different at D3 and D1+D3 thresholds. Conclusions: The association of adjunct methods increased the validity of dental caries examination in an epidemiological setting. However, the potential of CL2BW (traditional caries detection methods) or visual exam performed under a more refined diagnostic criteria must be considered in dental caries epidemiological surveys.